Avaliação dos mecanismos associados ao efeito terapêutico de dieta rica em fibras solúveis na cicatrização de feridas cutâneas em camundongos – papel do receptor GPR43 e da interleucina (IL)-18 - Puebla Cassini Vieira (2018)
In this work, we evaluated the effects of dietary supplementation with soluble fiber on the healing of cutaneous wounds, as well as the contribution of the G protein-coupled receptor (GPR43), also known as free fatty acid receptor 2 (FFAR2), and of the interleukin 18 (IL-18) for these effects. Wild-type C57BL/6 or gene knockout mice for GPR43 (Gpr43-/- ) or IL-18 (IL18-/- ) were fed with modified AIN-93 diet containing low (LF-Low Fiber) or high soluble fiber (HF) contents and submitted to the removal of 5- mm diameter cutaneous fragments from the thoraco-dorsal region for the creation of excisional lesions in the skin. The WT-HF group showed accelerated wound closure, reduction in neutrophil content and increased macrophages, and levels of TNF, IL-1, IL-18, IL-4 and IL-10, increased angiogenesis, and reduced collagen content and scar area in wounds when compared to the WT-LF group. Similar results were observed when we evaluated the effects of acetate, a GPR43 short chain fatty acid ligand that is produced in greater amounts by the metabolization of fibers by the intestinal microbiota. To that, we used the experimental model of granulation tissue formation induced by the subcutaneous implantation of a 8-mm diameter polyesterpolyurethane sponge matrix in the dorsal region. Oral, but not intra-implant treatment, with acetate, stimulated angiogenesis, reduced neutrophil infiltration and increased macrophage as well as reduced collagen production. Interestingly, the effects of the high soluble fibers diet were abolished in both Gpr43-/- and in IL18-/- mice. In order to better understand the role of IL-18 in wound healing, WT and IL18-/- mice, fed with standard diet, were submitted to the two abovementioned experimental models. IL18- /- mice presented delayed closure of cutaneous wounds, as well as reduction in all granulation tissue components, such as neutrophil and macrophages infiltration, number of blood vessels and collagen content, in both models, without, however, altering the scar area in the cutaneous wounds when compared to the WT mice. Finally, in order to investigate the main source of IL-18 involved in the effects of the high soluble fiber diet on the healing of cutaneous lesions, chimeric animals were created after bone marrow transplantation from WT mice to 8-Gy-irradiated WT-HF, WT-LF and IL18-/- -HF mice or from IL18-/- mice to irradiated WT-HF. Delayed skin wound closure was observed in WT-HF mice bearing IL18-/- hematopoietic cells when compared to WT-HF mice harboring WT hematopoietic cells. Taken together, our data suggest that dietary supplementation with a high content of soluble fiber accelerates skin wound closure in both GPR43-dependent manner and bonemarrow-derived IL-18-dependent manner. This work not only contributes to the knowledge of the impact of microbiota, short chain fatty acids and IL-18 on the healing of cutaneous wounds, but also presents an innovative, safe and economical alternative for the treatment of cutaneous wounds through dietary supplementation with soluble fibers.